A Comparative evaluation of smear layer removal using: sonic, ultrasonic, and erbium, chromium: yttrium scandium gallium garnet Laser as activated irrigation techniques (an SEM study) . - Dara Zakaria Shakir; Ihsan Neimat Bahnam (Erbil Dental Journal)
Background and Objectives: In root canal treatment it is important to provide a reliable method that effectively removes the smear layer to ensure more successful results in endodontic treatment. This study aims to compare the efficacy of different irrigant activation methods (sonic, ultrasonic, and erbium, chromium: yttrium scandium gallium garnet Er,Cr:YSGG—2780nm laser) for the removal of smear layer at coronal, middle, and apical one-third of the root canal surface.